Improving the maternal experience: watching your baby being delivered during caesarean section. (16th November 2010) - Field, K; Saadeh, F; Hewitt, M; O'Reilly, B; Keogh, J
Abstract : Changes in peripartum care have significantly improved maternal and fetal outcome with decreases in morbidity and mortality. This medicalisation of labour has increased the Caesarean section rate. Delivery by Caesarean section in this unit is approaching 30%, including both elective and emergency procedures. Caesarean sections are associated with delay in skin to skin contact, in initiation of breast feeding and problems in infant-maternal bonding. Furthermore, parents feel excluded from the process of child birth. Little has been done to improve the delivery experience for parents other than a shift from general to regional anaesthesia which was driven by safety issues rather than patient choice. The maternity theatres in the Cork University Maternity Hospital are equipped with audiovisual facilities which allow the birth process to be filmed, thus enabling both the patient and partner to simultaneously view the delivery as it happens without affecting the surgical field are altering the position of the patient during the operation. The authors looked at 24 patients and their experience with watching their baby being delivered. Of the deliveries, 79% were elective repeats, 83% of mothers enjoyed the experience, 12.5% were unsure and 4% did not enjoy the experience. Of the mothers who were having repeat sections 94.7% felt it enhanced their experience, 96% said they would repeat the experience if they were to have a repeat Caesarean section, and 96% would recommend the experience to a friend.